Sustaining linkages to high value markets through collective action in Uganda: the case of the Nyabyumba potato farmers - Kaganzi, Elly; Ferris, Shaun; Mulema, Annet A.; Sanginga, Pascal C.; Njuki, Jemimah; Barham, James (International Food Policy Research Institute, 2008)
Uganda's rapid urbanization, particularly in the capital city Kampala, offers new market opportunities for organized farmers to supply higher value produce for emerging growth markets such as multinational supermarket chains and fast food restaurants. Higher urban incomes allow consumers to shift from small shops and street food stalls to more formalized markets and modern food restaurants. These more formal market outlets provide both food safety and greater choice of produce. Supplying these outlets offers both higher income and improved business relations for farmers, but accessing these markets also requires significant upgrading in terms of product quality, more secure supply chains, and more efficient marketing and business management. To meet these conditions, farmers need to become organized for a marketplace that requires increased levels of bonding social capital to meet upgrade conditions and strengthened bridging social capital through partnerships with service providers and market chain actors to engage with these higher value markets in a long-term manner. One farmers' association in a remote rural area in Southwestern Uganda has successfully sustained market links through sales of high quality Irish potatoes to a fast food outlet in Kampala. To meet the volumes, frequency of supply, and quality parameters demanded by their client, the farmers have had to learn a series of new skills and integrate multiple innovations at the technical, organizational, financial, and marketing levels, and meet many of the classical conditions associated with collective action based on empowerment through social and human capital development. This paper outlines how the use of collective action combined with strong leadership and an iterative market-led learning process have enabled a smallholder farmer's association to supply a perishable crop to a modern food outlet market with stringent quality parameters. Success in this market linkage was possible through effective support from both development and research providers and the strong entrepreneurial drive from the farmer association.